Irregular Proton Injection to High Energies at Interplanetary Shocks - Trotta,D; Horbury,TS; Lario,D; Vainio,R; Dresing,N; Dimmock,A; Giacalone,J; Hietala,H; Wimmer-Schweingruber,RF; Berger,L; Yang,L (The Astrophysical Journal Letters, 2023)
Abstract How thermal particles are accelerated to suprathermal energies is an unsolved issue, crucial for many astrophysical systems. We report novel observations of irregular, dispersive enhancements of the suprathermal particle population upstream of a high-Mach-number interplanetary shock. We interpret the observed behavior as irregular “injections” of suprathermal particles resulting from shock front irregularities. Our findings, directly compared to self-consistent simulation results, provide important insights for the study of remote astrophysical systems where shock structuring is often neglected.